O relacionamento entre pilares institucionais e o desempenho logístico de uma rede de instalações pública - Regina Celia Nazar Fialho (2014)
Owing to the fact that public organizations give preference to institutional criteria for obtaining legitimacy , the aim of this study is to understand the influence of institutional components in the configuration and logistics performance of a network of public facilities . This is a quantitative piece of research, descriptive in nature, in which the method of survey research was used , the explanatory type , cross - sectional , complemented by desk research . The unit of analysis of the study in question was the pharmaceutical assistance program: Programa Farmácia de Minas. The units of observation are the institutional pillars present in Programa Farmacia de Minas and the performance of the network logistics used in the distribution of medications in the program. For the treatment and analysis of the data collected , the research used the Structural Equation Modeling , using the technique of exploratory factor analysis and confirmatory factor analysis . The study found that compliance of installations to institutional components of regulative character that deal with the rational use of medicines and optimization of the distribution system significantly affect the performance and the configuration of the installation network used in the distribution of medications . Institutional components of normative character affect neither the logistical performance nor the network configuration . And the institutional components of cognitive character affect the logistical performance as well as the configuration of the network facilities . As there is a causal relationship between the network design and logistics performance, a mediating effect of the network design in the relationship between institutional components and logistic network performance was found . The results presented in the study show the importance of the configuration of installation networks in the distribution and management of public networks as well as the impact of non-economic aspects in logistic performance.